PUBLICIDADE E O CONSUMO INFANTIL: Uma abordagem crítica - Machado, Alexandre (2014)
The contemporary childrens society of consumption presents numerous quotations involving the theme advertising and childrens consumption. Its complexity divides opinions, favorable and unfavorable, about the legitimacy, ethics and morals of advertising directed to children. This thesis presents the current situation of Brazilian childrens advertising and how children think, engage and influence unplanned consumption. The constitution of the Brazilian childrens scenario was developed in three stages: the first one was built a panel of childrens advertising with a analysis of 19 scientific articles from all regions of Brazil, that enabled the understanding and vision of the main Brazilian researchers on the subject, as was, 433 children, 6-12 years of the socioeconomic class A/B in the city of Santos, South Coast of São Paulo, were heard, projecting the reality that advertising exerts on childrens consumption and unplanned purchase, in children´s opinion. In the second stage, experts from various fields and segments of society, which are directly related to younger audiences, who contributed with opinions, critiques and visions of this behavioral trend of modern children. In the third and final stage, were heard through interviews, the parents in order to understand how and in what way they witness and contribute to the unplanned purchase of their children. The result reveals the main causes and effects that advertising directed to children provides the consumation and social behavior of the children and family (experts opinion), the co-responsible of these effects and what it is expected for ethical consumption scenario of children Brazilian.